Effect of glide on neuromuscular adaptation in breaststroke swimming: a case study of an elite swimmer - Conceição, Ana (2018)
The aim of this case study was to examine the upper and lower limbs muscular responses of one elite breaststroke swimmer at three different glide and speed conditions, to understand how strength and condition could be optimized during training. Surface electromyograms (sEMG) were collected in biceps brachii (BB), biceps femoris (BF), deltoid anterior (DA), gastrocnemius medialis (GM), pectoralis major (PM) rectus femoris (RF), tibialis anterior (TA), and tríceps brachii (TB) during 18 x 25 m breaststroke trials performed at three different glide( normal, maximal, minimal) and speed (70, 80 and 90% of maximal speed) conditions. Each trial required an individually imposed swimming speed corresponding to 70, 80 and 90% of the swimmer maximal speed and a specific glide condition: minimal glide, normal glide and maximal glide. In maximal glide, higher participation of TB and DA and TA, RF, and GM muscles. In normal glide, a significant higher participation of all the muscles occurred, except for GM. In minimal glide, a significant higher participation of all the muscles occurred, except for the PM. We have also found that swimming at 90% of maximal speed led to significant higher use of the BB and PM muscles, for the upper limbs and BF and TA muscles for the lower limbs. In conclusion, the swimmer recruited different muscles as increasing his swimming speed and when gliding differently than normally. It suggested that strength and condition should be trained for various swimming speeds associated to various conditions of glide to ensure behavioral adaptability in competition.